Flow‐based electromagnetic‐type energy harvester using microplanar coil for IoT sensors application. (13th June 2019) - Ahmad, Iftikhar; Ur Rehman, M. Mohib; Khan, Masroor; Abbas, Ahmad; Ishfaq, Sarmad; Malik, Sohail
Summary: Battery is the sole power source for Internet of thing (IoT) sensors. Due to limited shelf life, the batteries are required to be replaced intermittently. This periodic replacement of batteries is inflated in terms of both logistics and time. This article illustrates conceptual design, development, and characterization of a flow‐based electromagnetic‐type energy harvester (F‐EH) using microplanar coil for IoT sensors application. The F‐EH converts hydro energy into useful electrical energy utilizing electromagnetic transduction mechanism. The microfabrication and macrofabrication techniques adopted to manufacture harvester's components are presented. The F‐EH has been successfully characterized by laboratory scale experimental flow test loop commissioned for this work. Experimentation with associated uncertainty analysis prevails that at a matching impedance, the F‐EH can generate a 686 μW of maximum power at an operating flow rate of 12 L/min with an uncertainty of 8.1%. Abstract : The developed prototype is a novel contribution in terms of its capability to scavenge hydro energy and convert it into useful electrical energy at the microlevel to operate wireless sensors nodes used in Internet of things applications. Printed circuit board (PCB)–based double‐sided microplanar coils of the developed prototype are able to deliver output power at low flow rates.